Scientific research title-its importance and controls (مجلة أبحاث قانونية, 2023)
The principle is that the title of the research clearly indicates its content and reveals its content. But this may not always be achieved, so the title is criticized either for its shortcomings, or for its capacity, or for its inconsistency with the subject and plan of the research, or for the lack of formal or objective controls in it. In order for the title of the scientific research to be good and disciplined, there must be controls in its form and in its subject, but before that, the title must be defined and its importance indicated, so that this is reflected in its controls, and this is what I have been studying in this research.
Keywords: title; theses; controls